2019
DOI: 10.7717/peerj.6274
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nickel and cobalt on methane production and methanogen abundance and diversity in paddy soil

Abstract: BackgroundPaddies are an important anthropogenic source of methane emissions to the atmosphere, and they are impacted by heavy metal pollution. Nickel (Ni) and cobalt (Co) pollution might either enhance or mitigate CH4 emission from paddy soils due to the total amounts of metals, bioavailability and functional microbial activity and composition.MethodsAn incubation experiment was conducted, and different Ni and Co concentrations were added to test the effects of trace metals on methane production in paddy soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…Considering that cobalt concentrations were very low in the studied sites, increase in such concentrations positively increased CH 4 production by promoting methanogens. Similar positive correlation was also observed in paddy fields, where cobalt promoted the abundance and activity of methanogens (Wang et al., 2019). The same study also found that optimum cobalt concentrations for CH 4 production in paddy soil are 50 mg kg −1 , which is multi‐fold higher than the concentrations in studied tropical peatlands, showing a strong potential for further increase in CH 4 emissions with changes in cobalt concentrations.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…Considering that cobalt concentrations were very low in the studied sites, increase in such concentrations positively increased CH 4 production by promoting methanogens. Similar positive correlation was also observed in paddy fields, where cobalt promoted the abundance and activity of methanogens (Wang et al., 2019). The same study also found that optimum cobalt concentrations for CH 4 production in paddy soil are 50 mg kg −1 , which is multi‐fold higher than the concentrations in studied tropical peatlands, showing a strong potential for further increase in CH 4 emissions with changes in cobalt concentrations.…”
Section: Resultssupporting
confidence: 76%
“…The concentrations of these nutrients and heavy metals in peat can influence greenhouse gas emissions via a few different pathways: (a) directly through chemical and mechanistic control over processes (Warren et al., 2017); (b) indirectly through changes in microbial community properties such as community structure, diversity, activity and biomass (Dowrick et al., 2006; Wang et al., 2019); (c) in natural habitats, nutrients and trace elements can also influence plant species distribution (John et al., 2007) that affects microbial communities through rhizosphere or plant litter inputs, which can further impact GHG emissions (Bezemer et al., 2006; Burns et al., 2015; Fan et al., 2019). However, the lack of research on nutrient and trace element concentrations in different peatlands, particularly tropical peatlands leave these processes and interrelations unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…However, very high concentrations of nickel have also been associated with detrimental effects on methanogens and methane productions (Chen, Cheng and Creamer 2008). Peatlands with low concentrations of nickel have communities dominated by Methanocellales and Methanosarcina, suggesting that these methanogenic groups may be inhibited by higher concentrations of nickel in soil (Figure S4, Supporting Information; Paulo et al 2017;Wang et al 2019). In contrast, the Methanomicrobiales appear to thrive with elevated concentrations of nickel, possibly due to the diversity of Methanomicrobiales, effective mechanisms for regulating or tolerating metal uptake, or other factors in the environment that covary with the high metal concentrations, such as Sphagnum loss in the three impacted sites, Long, Daisy and Whitson (Carson 2018).…”
Section: Environmental Influence On Methanogen Community Compositionmentioning
confidence: 99%
“…Shi et al [55] observed that, in the treatment of lignocellulosic biomass, a prior acclimation period of the microbes contained in the inoculum was necessary for immediate biogas production in digesters. Additionally, a sufficient contact time reduced the magnitude of the microbial response to potentially toxic compounds, namely excessive levels of ammonia, volatile fatty acids, and heavy metals that can exert bacteriostatic and even bactericidal effects [56][57][58].…”
Section: Impact Of a Fill-and-draw Inoculummentioning
confidence: 99%